PENGARUH VARIASI JUMLAH BLADE TURBIN ANGIN TERHADAP OUTPUT DAYA LISTRIK - Wiratama, I Kade; Mara, Made; Mulyanto, Arif; Harianhady, Muliadi (Universitas Mataram, 2014)
Some area in Indonesia such as southern part of Sumatra to Nusa Tenggara have big enough wind speed to produce electrical energy by using wind turbine. However, the potential resources are not yet fully developed, and only 1.4 GW electrical energy has been generating in the Indonesia region. Most of the wind energy generating equipment is designed to the European wind speed which is 10 - 30 knot. So, it is very important to modify the such equipment to be able to implement in Indonesia area which is have a lower wind speed.The purpose of this research is to know the influence of number of blades and wind speed to electricity generated by horizontal axis wind turbine with blade taper inversed linear.The result showed that the highest electrical output power was 2,02 watt produced by 5 blades and 3,5 m/s wind speed. The lowest electrical output power was 2,347 watt achieved by using 3 blades and 2,5 m/s wind speed.